2020
DOI: 10.3390/math8101758
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Investigation of Poly-Jet 3D Printing

Abstract: An experimental investigation of the surface quality of the Poly-Jet 3D printing (PJ-3DP) process is presented. PJ-3DP is an additive manufacturing process, which uses jetted photopolymer droplets, which are immediately cured with ultraviolet lamps, to build physical models, layer-by-layer. This method is fast and accurate due to the mechanism it uses for the deposition of layers as well as the 16 microns of layer thickness used. Τo characterize the surface quality of PJ-3DP printed parts, an experiment was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The "nntool" toolbox (MATLAB R2015) has been used to develop the FFBP-NN model. For similar mechanical applications, where the performance metrics have to be assigned according to the input parameters, a simple FFBP-NN with one hidden layer is considered adequate [40]. The typical BackPropagation (BP) algorithm is used for the NN training procedure.…”
Section: Ffbp-nn Set Upmentioning
confidence: 99%
“…The "nntool" toolbox (MATLAB R2015) has been used to develop the FFBP-NN model. For similar mechanical applications, where the performance metrics have to be assigned according to the input parameters, a simple FFBP-NN with one hidden layer is considered adequate [40]. The typical BackPropagation (BP) algorithm is used for the NN training procedure.…”
Section: Ffbp-nn Set Upmentioning
confidence: 99%
“…They used 0, 15, 30, 45, 60, 75 and 90° slope values and the X and Y direction as experimental inputs. Results showed that parts produced in the X direction showed better surface roughness when the sloped surface angle was below 45° and, after that value, parts produced in the Y direction had lower surface roughness values [ 43 ].…”
Section: Process and Materialsmentioning
confidence: 99%
“…This technology is defined as a process in which droplets of construction material are selectively deposited. These droplets can be a liquid photoplomer or a fused wax, and are solidified through a radiation light source by chemical reaction [ 114 ]. This procedure can be seen in the video [ 95 ].…”
Section: Appendix A1 Directed Energy Depositionmentioning
confidence: 99%